Developing problem-based learning worksheet of relations and functions topic to support students’ conceptual understanding - Pratiwi, Weni Dwi; Zulkardi, Zulkardi; Putri, Ratu Ilma Indra; Hiltrimartin, Cecil (Jurnal Gantang, 2024)
This research is qualitative research with design research methods and a development research type aiming to produce valid and practical worksheets on relational and functional materials based on problem-based learning (PBL) to support students' conceptual understanding. The learning process is carried out in the classroom with learning activities, accompanied by a student's worksheet, which consists of 2 questions. The subjects of this study were students of class VIII 10 of SMP Negeri 8 Palembang, with 6 students as the focus of the research. There are 2 stages in this research, namely: (1) preliminary stage and (2) prototyping stage (formative evaluation), which is divided into 5 stages, namely (1) self-evaluation, (2) expert review, (3) one to one, (4) small group and (5) field test. This research was conducted based on the learning system in schools with data collection techniques, namely walkthroughs, tests, interviews, and questionnaires, to be collected and analyzed qualitatively to see the validity and practicality of the worksheet. The results of this study will show that the worksheet that has been made is valid, as seen from the results of the expert review and practical validation sheets obtained from the questionnaire results, with an average of 84.03%, which is included in the valid and practical categories. The developed worksheet also supports understanding PBL-based concepts (Problem-Based Learning) in solving problems given in relation and function material, which can be seen from the overall student test results.